Gas Sensing Behavior of Mesoporous SiOC Glasses. Issue 8 (30th July 2013) - Karakuscu, Aylin; Ponzoni, Andrea; Aravind, Parakkulam R.; Sberveglieri, Giorgio; Soraru, Gian D.; Kleebe, H.‐J.
<x xml:space="preserve">Abstract</x> In this study, for the first time, we report the gas sensing behavior of aerogel‐derived silicon oxycarbide (SiOC) glasses. The SiOC glass pyrolyzed at 1400°C has specific surface area of 150 m2/g with pore size in the 2–20 nm range. SiOC sensor shows good response to 5 ppm NO2 at 300°C. NO2 response completely disappears at 400°C, and from this temperature SiOC sensor starts respond to H2. The optimum sensitivity for H2 is obtained at 500°C. SiOC sensor is very selective; it is not sensitive to other gases such as acetone vapor or CO, even at high concentrations.